Analisis Pengembangan Kurikulum Cambridge dalam Pembelajaran Matematika dengan Project-Based Learning di Sekolah Dasar Islam - Fatimah, Laeli Siti; Fatayan, Arum (Jurnal Paedagogy, 2022)
This study aims to analyze the development of the Cambridge curriculum in Mathematics learning with project-based learning in elementary school. This research was conducted using a qualitative case study approach. Data collection in this study involved a 3rd-grade teacher who taught the Cambridge curriculum and one of the 3rd-grade students as an informant. Data collection techniques were carried out using observation, interviews, and documentation. This study was analyzed using Miles and Huberman’s data analysis techniques, namely data reduction, data presentation, and drawing conclusion and verification. The research showed that applying the Cambridge curriculum in mathematics learning with project-based learning provides meaning for students in Islamic elementary schools in absorbing learning materials, mastering concepts, creativity, and student activity. The results of this research impact the teaching and learning process that prioritizes the needs of students according to their age, and parental support influences children in getting a lesson.